The Values of Local Wisdom Contained in the Dieng Culture Festival (DCF) in Banjarnegara to Build National Character - Nailatul Fauni, Rizky; Sukmayadi, Trisna (Jurnal Penelitian Ilmu-Ilmu Sosial, 2022)
Culture has a fairly broad scope, one aspect that is closely related to culture is local wisdom which contains many values in it. This research is motivated by the negative influence of the globalization era, namely consumptive lifestyles, individualistic attitudes, westernized lifestyles and social inequality. The purpose of this study was to determine the values of local wisdom contained in the Dieng Culture Festival (DCF) in Banjarnegara to build the character of the nation. This research is a descriptive qualitative research. Data collection techniques using interviews and documentation. The data analysis technique uses data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that the values of Local Wisdom contained in the Dieng Culture Festival (DCF) in Banjarnegara to build the nation's character are that (1) The implementation of the Dieng Culture Festival which consists of various activities such as cultural carnival, cutting dreadlocks children's hair, ngalab procession Blessings, lantern and jazz festivals have a special meaning in each of their activities. (2) The values of local wisdom contained in the Dieng Culture Festival are religious values, aesthetic values, mutual cooperation values, tolerance values and moral values. (3) The values of local wisdom contained in the Dieng Culture Festival can be used to build the nation's character. However, there is a need for strong education in the community, a sense of caring for others and a positive mindset for everyone.